"When I Am a President of Guinea": Resettled Refugees Traversing Education in Search of a Future. Issue 4 (2nd October 2017) - Dryden-Peterson, Sarah; Reddick, Celia
Abstract : This article explores how resettled refugees' aspirations cultivated through education collide with postschooling realities. We find that post-graduation barriers of financial insecurity, housing insecurity, violence and discrimination, and lack of critical awareness of unequal opportunity structures stand in the way of resettlement aspirations. We discuss how teachers and schools might be retooled to equip refugee students with more and different skills to navigate post-graduation situations.